Xanthine Oxidase Inhibitors the Unappreciated Treatment for Heart Failure - Ellestad, Myrvin H. (Cardiovascular & Haematological Disorders - Drug Targets, 2007)
The recognition that uric acid plays a significant role in cardiac function has been slow to be appreciated. About 50 years ago it was recognized that gout and high uric acid levels were often a marker for coronary heart disease, Since then the literature has contained several hundred studies which have demonstrated a great deal of the physiology of xanthine oxidase inhibition. A reduction in xanthine oxidase improves cardiac output, improves endothelial function, reduces myocardial infarct size, reduces inflammation, reduces myocardial oxidative stress and platelet adhesiveness. It seems logical that these effects would be beneficial to patients with congestive heart failure. A large placebo controlled trial with Allopurinol seems very likely to demonstrate that this old fashioned drug provides a new found benefit.
Keywords: oxypurinol